The Contribution of Personality in Predicting Applicants’ Motivation to Fake Non-Cognitive Measures - Tonković Grabovac, Maša (2011)
In context of personnel selection, faking can be defined as a “tendency for test takers to deliberately provide inaccurate responses to personality items in a manner that they believe will increase their chances of obtaining valued outcomes, such as favorable hiring decision”. Research has shown that candidates differ regarding this tendency, as well as selection programs regarding the level they make faking possible and probable. Hence, faking can lower the predictive validity of personality questionnaires and reduce the quality of selection decisions. Given the fact that faking is a behavior that cannot easily be detected, it is important to better understand the underlying psychological process, i.e. find the factors that determine the occurrence and the intensity of faking behavior. In the last decade several authors have systemized potential factors and suggested models that specify key determinants of faking behavior and relationships among them. Even though these models vary regarding both the specified determinants and quality of their relationships, there are several elements they all have in common. One of them is the important role of applicants’ personality in predicting applicants’ motivation to fake and consequently faking behavior. Some people are more prone to faking across many situations, while some will not be willing to fake even in situations that make it easy. Hence, faking behavior in personnel selection should be to certain degree determined by the candidate’s stable individual characteristics – personality.
Projekt MZOS
ENG